If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n in (-oo:+oo)
-7*n-6 = -69 // + 69
69-7*n-6 = 0
63-7*n = 0 // - 63
-7*n = -63 // : -7
n = -63/(-7)
n = 9
n = 9
| 2k-7=9 | | -6b+1=-53 | | -2d-9=-13 | | 3+4k=-33 | | 2+4m=2 | | 1-3m=-26 | | 5x(3x-2)=0 | | -8-6m=-80 | | -4d-8=-52 | | 7d+4=-24 | | -6t-10=-34 | | 1(x)=2x-1 | | 2n-6=-16 | | 1+7x=-83 | | -6m-7=-31 | | 4-2n=-14 | | 2n+9=-9 | | -3a+7=19 | | 4n+1=-3 | | 5m+10=15 | | 3t+3=-21 | | -4k+1=-15 | | 2d-6=14 | | -7n-2=-44 | | 4+4n=-32 | | 5d+3=33 | | -7+5w=-7 | | 2t-6=14 | | 3w+9=33 | | 7-4d=39 | | -6b-7=-49 | | 1+6m=-11 |